Analisis Technology Acceptance Model (TAM) Berdasarkan Partisipasi UMKM Perempuan: Kajian Studi Kota Padang - Sri Mona Octafia; Elsa Widia (Universitas Negeri Padang, 2023)
MSMEs have developed and become a key pillar in the national economy. Nevertheless, women's participation in MSMEs is still limited, despite the fact that women have a lot of potential to boost the economy through SME ownership. The positive attitude of women in MSMEs towards the adoption of technology is among the parameters that might have influenced their usage of technology. In the present day of transforming communication and information technologies, the acceptability of technology is becoming increasingly essential for the continuing development of MSMEs. The aim of this study is to use the Technology Acceptance Model (TAM) to examine how women's participation in MSMEs relates to their acceptance of technology in the Koto Tangah Padang region. A paradigm called the Technology Acceptance Model (TAM) is used to describe how people understand and utilize information technology systems. The method used involves the application of SEM PLS 4.0. Primary data was collected through questionnaires and structured interviews. The results of the research indicate that women in MSMEs' degree of trust in technology is significantly influenced by their perceptions of perceived security and simplicity of use. Additionally, It has been proven to be the most influential factor influencing women in MSMEs' intentions to use technology for their businesses is trust.